2022
DOI: 10.5114/aic.2022.121033
|View full text |Cite
|
Sign up to set email alerts
|

Trans-endocardial delivery of progenitor cells to compromised myocardium using the “needle technique”and risk of myocardial injury

Abstract: Introduction:Recent studies indicate that the therapeutic effects of endocardial cell transplantation in chronic heart failure (iCHF) may be lost with an increasing number of injections.Aim: To evaluate global and regional contractility and diastolic function of the left ventricle of patients with advanced iCHF who received endomyocardial cardiopoietic mesenchymal stem cells (MCSs) or sham procedures.Material and methods: The study included patients (mean age: 60.8 ±7.1 years) with iCHF (left ventricular eject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, larger studies are required to corroborate our present findings. Furthermore, while there is no doubt that a parallel sham/placebo comparative cohort would be desirable [ 8 , 46 ], the sample size in our study of labelled cells did not justify a control sham/placebo group.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, larger studies are required to corroborate our present findings. Furthermore, while there is no doubt that a parallel sham/placebo comparative cohort would be desirable [ 8 , 46 ], the sample size in our study of labelled cells did not justify a control sham/placebo group.…”
Section: Discussionmentioning
confidence: 95%
“…However, there is still a research gap in this field. Dravik et al. (2022) indicate the need to support “a better understanding of the causes, interlinkages, and impacts of environmental stressors on health and the environment.” The primary question concerns the relationship between the health system and public policies (environmental, research, etc.).…”
Section: Theoretical Foundation Of the Study And Research Gapmentioning
confidence: 99%
“…On the other hand, this type of cell implantation is not physiological and may be of limited value in terms of further cell survival. However, myocardial injections may cause myocardial damage [ 60 ]. Data from the Congestive Heart Failure Cardiopoietic Regenerative Therapy (CHART-1) trial indicated an association between an increase in the number of endomyocardial injections to deliver therapeutic cells and a reduction in the therapeutic effect of mesenchymal cell transplantation in patients with chronic ischemic heart failure [ 61 ].…”
Section: Routes Of Cell Administration To Myocardiummentioning
confidence: 99%